NU DI TENGAH PUSARAN IDEOLOGI-IDEOLOGI TRANSNASIONAL - Husni, Zainul Mu’ien (JURNAL ISLAM NUSANTARA, 2018)
This paper presents the existence of Nahdlatul Ulama' (NU) in the midst of the emergence of a new flow and ideology that developed in Indonesia. Although Indonesia is not an Islamic ideology, the growing Islamic population in Indonesia makes Indonesian Muslims an easy target for activists of Islamic movements from outside Indonesia to campaign for their movement to become a major movement in Indonesia. Currently, there are many streams and religious ideologies which are crucially opposed to Ahlus Sunnah wal Jamaah (ASWAJA), such as Shia, Wahabi, Hizbut Tahrir, or known as Islam Transnasional, a movement that is not native to Indonesia. The existence of this political organization is not born from the struggle of identity to Indonesia-an authentic, but rather moved, taken or imported from other countries that tend not to fit the context to Indonesiaan. Islam Transnasional is another name for radical Islam, Islam Kanan, Islamic fundamentalism and puritanical Islam. Ironically, they came at almost the same time, thereby posing a challenge for Nahdlatul Ulama 'organization in its organizational development and dakwah. Therefore, each of these groups makes the Nahdlatul Ulama residents' targets to be recruited into their cadres. Therefore, we need to be alert to the organization, so the unity of the Unitary State of Indonesia remains intact and maintained in accordance with the purpose and desire founding father